Prioritizing sweetpotato in the context of roots, tubers and bananas - International Potato Center (2016)
The CGIAR Research Program on Roots, Tubers and Bananas (RTB) brings together four CGIAR centers - Bioversity International, the International Center for Tropical Agriculture (CIAT), the International Potato Center (CIP) and the International Institute of Tropical Agriculture (IITA) - and CIRAD (also representing the French organizations IRD, INRA, and Vitropic) with more than 350 partners for research on banana, cassava, potato, sweetpotato, yam, and minor roots and tubers. The program has two dedicated clusters of activity on sweetpotato, led by CIP scientists, that will interact with, learn from, and add critical mass to RTB’s other work.